German farmers' acceptance of subsidized insurance associated with reduced direct payments. Issue 3 (3rd June 2019) - Möllmann, Johannes; Michels, Marius; Musshoff, Oliver
Abstract : Purpose: The outstanding reform of the Common Agriculture Policy allows for changes regarding its most criticized component, the direct payment scheme. The purpose of this paper is to investigate farmers' acceptance of subsidized whole farm income insurance (WFI) and single-crop, multi-peril revenue insurance (RI) that are associated with a reduction of direct payments. Design/methodology/approach: By applying a generalized multinomial logit model on data of a discrete choice experiment, German farmers' preferences, expressed as their willingness to pay (WTP), for WFI and RI are revealed. Findings: The results show a positive WTP for WFI and RI. The average farmer has a higher WTP for WFI than for RI. By increasing the coverage level, the negative influence of a reduction of direct payments on WTP for insurance can be compensated. Individual risk attitude and assessed importance of direct payments for the farm business show a statistically significant influence on the WTP. Practical implications: The results suggest that, even if direct payments were abolished in order to subsidize WFI or RI, German farmers' WTP for both insurance products would remain positive. However, to finally assess whether subsidizing insurance is the right means of providing public support, it is necessary to assess whether farmers' WTP meets the costs for such an insurance scheme. Originality/value: To the authors' knowledge, this is the first study investigating German farmers' WTP for WFI and RI using an experimental approach by explicitly considering the partial to complete replacement of direct payments by subsidized insurance.